THE MOST USED IDIOMS IN ENGLISH AND THEIR ALTERNATIVES IN UZBEK (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
One of the most challenging issues in translation is translating idioms from one language to another conveying their connotation and denotation meanings. In this article, the phrases used in English are given, and their equivalents in Uzbek are also described.